Changes in myocardial work associated with pediatric kidney transplantation: A pilot study of short‐term postoperative effect. Issue 12 (11th November 2022) - Xiao, Fei; Fan, Rui; Zhang, Jingwei; Ye, Min; Li, Wei; Liu, Donghong; Liu, Longshan; Yao, Fengjuan; Lin, Hong; Li, Cuiling
Abstract: The study was mainly to evaluate the changes of left ventricular (LV) myocardial work (MW) in children with CKD stage 5 within 3 months after kidney transplantation (KTx). Forty‐three successful KTx recipients (mean age 10.6 years, 58% male) in childhood and 28 healthy children were enrolled. General clinical characteristics and laboratory parameters were collected. Cardiac structure, function, and LV MW were assessed by echocardiography before and after KTx. The results showed that significantly improvement was observed in LV global MW index (GWI), constructive MW (GCW), and wasted MW (GWW) ( p < .01), but not in MW efficiency (GWE) and global longitudinal strain (GLS) ( p > .05). Besides, blood pressure (BP), renal graft function, LV ejection fraction (LVEF), and LV mass index (LVMi) had obviously improved after KTx ( p < .05). Nevertheless, compared with healthy children, higher BP, LVMi, GWW, more deteriorated LV diastolic function and lower GWE were still observed in patients after KTx. The ratio of dialysis duration to CKD course were negatively correlated with the improvements of GWE ( p = .004), GWI ( p = .01), and GCW ( p = .01). In conclusion, a portion of LV MW parameters were obviously improved in children received KTx. Thus, LV MW was superior to GLS in evaluating LV systolic function recovery in these patients. Those patients with insignificant MW improvement should be closely monitored, and adjusted the treatment strategies timely to avoid serious and irreversible myocardial injury after KTx.